THE CONTRIBUTION OF SCHOOL PRINCIPALS' LEADERSHIP IN REALIZING EXCELLENT ELEMENTARY SCHOOLS: A LITERATURE REVIEW - Fauzan, Azzan; Sariwardani, Andriani; Dewi, Ratna (Cakrawala Pedagogik, 2025)
The leadership of school principals plays a strategic role in shaping the direction, culture, and quality of education in elementary schools. In the context of increasing demands for educational quality and global competitiveness, effective leadership has become more urgent in achieving high-performing elementary schools. This study aims to examine the contribution of principal leadership in realizing excellent elementary schools through a literature review approach. A systematic review was conducted using articles published between 2015 and 2024, selected based on relevance and sourced from nationally and internationally accredited journals. Thematic analysis was employed to identify leadership patterns and practices that contribute to school excellence. The findings reveal that transformational, participatory, and vision-oriented leadership significantly contributes to improving teacher performance, parental involvement, school climate, and student achievement. These results suggest that effective principal leadership is a key factor in the sustainable development of elementary school quality. Therefore, strengthening principal leadership capacity should be prioritized in basic education policies.